Giáo trình tiếng Anh chuyên ngành lịch sử - Hoàng Ngọc, Anh (Trường Đại học Quảng Bình, 2017)
INTRODUCTION English for History is a book used for the students of History major. The book aims at providing students basic English knowledge for History through selected topics of three historical periods in the world and Vietnam: The Old Ages, The Middle Ages and The Modern Ages. The book consists of 8 units written in English. These units are designed to be suitable for students at pre-intermediate level or above. In total the book provides 45 periods of teaching. It includes a collection of useful texts and mainly Reading Comprehension, Vocabulary, Grammar Exercises and Writing. Besides, translation activities are also added to improve students’ English for professional purposes in the future. The book is expected to enable students to use English through historical events when they practice language skills.